2017
DOI: 10.1007/s00404-017-4517-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive prenatal testing (NIPT): Europe’s first multicenter post-market clinical follow-up study validating the quality in clinical routine

Abstract: NIPT provides a very high quality for the fetal trisomies 21, 13 and 18 in clinical routine. The results support the recommendation that NIPT should be offered after genetic counseling and only in conjunction with a qualified ultrasound examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Another question concerns the possible target groups for NIPT, which is also relevant for Estonia. It has been shown that there is no significant difference in NIPT screening performance between high‐risk, routine and mixed populations . Therefore, the question arises what is the better way to implement NIPT into clinical practice and who are the main target groups for this testing.…”
Section: Discussionmentioning
confidence: 99%
“…Another question concerns the possible target groups for NIPT, which is also relevant for Estonia. It has been shown that there is no significant difference in NIPT screening performance between high‐risk, routine and mixed populations . Therefore, the question arises what is the better way to implement NIPT into clinical practice and who are the main target groups for this testing.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the issue to what extent one should be tested, another question exists, regarding the possible target groups for NIPT, which is also relevant for Estonia. It was demonstrated that there is no significant difference in NIPT screening performance between highrisk, routine and mixed populations (30). Therefore, the question arises what is the better way to implement NIPT into clinical practice and who are the main target groups for this testing.…”
Section: Discussionmentioning
confidence: 99%
“…After its identification in 1997, a rapid increase in the use of cell-free fetal DNA analysis led to an awareness of the need for further development and implementation. There have been many studies into the use of cfDNA in maternal blood for the detection of trisomies 21, 18, and 13 in groups at high risk of aneuploidies [4,7,8]. A recent study showed excellent results when predicting aneuploidy in twin cases [9].…”
Section: Introductionmentioning
confidence: 99%